Avian influenza vaccine supply chain in Quang Ninh province, Vietnam, 2021 - Trong Duc Tran; Manakorn Sukmak; Waraphon Phimpraphai; Pawin Padungtod; Tippawon Prarakamawongsa; Long Thanh Pham; Minh Van Truong; Suwicha Kasemuwan (Veterinary Integrative Sciences, 2023)
Highly pathogenic avian influenza (HPAI) is a zoonotic disease that can affect both poultry and humans. Since 2005, the Vietnam government has implemented a national vaccination campaign to prevent the spread of avian influenza (AI). In 2021, the first outbreak of HPAI H5N8 was reported in a chicken farm in Quang Ninh province. To understand the stakeholders linked to the AI campaign, and their roles within the vaccine supply chain, we conducted a cross-sectional study from November 2021–January 2022. We purposively selected 114 participants, including 71 poultry farmers using HPAI vaccines, 16 veterinary drug store owners, 18 commune animal health workers (CAHWs), 8 staff from the Centers for Agricultural Services (ATSCs), and one vaccine distributor who were interviewed face-to-face using a structured questionnaire. Three HPAI vaccines (H5N1 clade 1 & 2.3.2.1, H5N1 clade 2.3.4 and H5N1 clade 2.3.2.1b) were used, and they were effective against the locally circulating virus strains. Distributors stored vaccines at the required temperature and transported them in appropriate vehicles. Vaccines remained in the supply chain for 3–5 months within their 12-month shelf-life period. The free government vaccination campaign, implemented by CAHWs, and administered by the ATSCs, reached 61% of small-scale poultry farms with a 1.21% vaccine wastage rate. Large-scale poultry farms followed the national campaign but paid a fee for the vaccines. We recommend expanding the support for AI vaccination to increase the vaccination rate among large-scale poultry farms, selecting higher efficacy seed vaccines, and that smaller dose vaccine vials are available for cost-effective vaccination.